2007
DOI: 10.1002/hep.21911
|View full text |Cite
|
Sign up to set email alerts
|

Decreased white matter lesion volume and improved cognitive function after liver transplantation

Abstract: Focal T2-weighted white matter lesions (WML) on brain magnetic resonance imaging (MRI), mimicking those seen in cerebrovascular small-vessel disease described in patients with persistent hepatic encephalopathy, decreased in volume with the improvement of hepatic encephalopathy. This outcome has been interpreted as a decrease in the edema that it is proposed to be involved in the pathogenesis of hepatic encephalopathy. We designed a study to further investigate potential changes in focal WML in the brains of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 33 publications
2
63
3
Order By: Relevance
“…104 Due to their location and small size, WMLs in patients with cirrhosis can be easily ignored or interpreted as normal involutive or chronic ischemic changes. However in patients with cirrhosis, these lesions decreased their volume with the improvement of HE 105 or after liver transplantation, 106 a fact that is closely correlated with the improvement of neuropsychological function (Fig 4). The partial reversibility of these focal WMLs is on the opposite side of what occurs with focal WMLs attributable to cerebrovascular small-vessel disease.…”
Section: Fast Flair Sequencesmentioning
confidence: 77%
“…104 Due to their location and small size, WMLs in patients with cirrhosis can be easily ignored or interpreted as normal involutive or chronic ischemic changes. However in patients with cirrhosis, these lesions decreased their volume with the improvement of HE 105 or after liver transplantation, 106 a fact that is closely correlated with the improvement of neuropsychological function (Fig 4). The partial reversibility of these focal WMLs is on the opposite side of what occurs with focal WMLs attributable to cerebrovascular small-vessel disease.…”
Section: Fast Flair Sequencesmentioning
confidence: 77%
“…To further investigate this observation, the same investigators compared WML volumes in patients with impaired cognition, pre-and post-liver transplantation (32). A significant reduction in WML volume was detected after liver transplantation (Figure 2), as well as a strong negative correlation between fast FLAIR T 2 -weighted lesion load and psychometric score.…”
Section: T 2 -Weighted Mri: Fast Flair Imagingmentioning
confidence: 97%
“…Furthermore, several studies in cirrhotic patients have showed a positive correlation between brain edema (evaluated by different magnetic resonance techniques) and scoring in neuropsychological tests Sugimoto et al, 2008). In addition, following liver transplantation in patients with MHE, a decrease in brain edema was associated with an improvement in cognitive function (Rovira et al, 2007).…”
Section: Role Of Brain Edema In Hementioning
confidence: 99%